Assessment of water distribution system capacity as settlement-development decision-making expert basis at local level (translation) - Ajda Kafol Stojanović; Daniel Kozelj; Maruška Šubic Kovač (Geodetski Vestnik, 2020)
Settlement development depends on many factors, including the availability of municipal infrastructure. Scientists find that only integrated municipal infrastructure planning and settlement-development planning create conditions for sustainable and economical urban development. This is not taken into account in spatial planning practise in Slovenia. This paper seeks a response to the research question: Based on what data, and based on what model can the capacity of the water supply system in Slovenia be assessed, which constitutes the expert basis for settlement development decision-making at the local level. To this end, we analysed the results of relevant existing research and devised an appropriate integrated and dynamic model for assessing the capacity of the water supply system, which was generated from a simulation of construction on vacant building land and relevant water requirements of new water consumers. In assessing the capacity of the public water supply system, the Aquis 7.0 Software was applied in accomplishing the hydraulic system validation. In line with the hydraulic system validation results, the respective measures are proposed, and the costs of necessary improvements of the existing water supply system or its upgrading are envisaged. Based on the results obtained, the settlement-development stages can be determined. The model for assessing the capacity of the water supply system was applied to the example of the Municipality of Kranj.